Transdisciplinary research and clinical priorities for better health. - Luigi Fontana; Alessio Fasano; Yap Seng Chong; Paolo Vineis; Walter C Willett (PLoS Medicine)
Modern medicine makes it possible for many people to live with multiple chronic diseases for decades, but this has enormous social, financial, and environmental consequences. Preclinical, epidemiological, and clinical trial data have shown that many of the most common chronic diseases are largely preventable with nutritional and lifestyle interventions that are targeting well-characterized signaling pathways and the symbiotic relationship with our microbiome. Most of the research priorities and spending for health are focused on finding new molecular targets for the development of biotech and pharmaceutical products. Very little is invested in mechanism-based preventive science, medicine, and education. We believe that overly enthusiastic expectations regarding the benefits of pharmacological research for disease treatment have the potential to impact and distort not only medical research and practice but also environmental health and sustainable economic growth. Transitioning from a primarily disease-centered medical system to a balanced preventive and personalized treatment healthcare system is key to reduce social disparities in health and achieve financially sustainable, universal health coverage for all. In this Perspective article, we discuss a range of science-based strategies, policies, and structural reforms to design an entire new disease prevention-centered science, educational, and healthcare system that maximizes both human and environmental health.